2021
DOI: 10.52547/jcmh.8.1.6
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Addictions to Computer Games with Sleep Disorder in Preschool Children: The Moderating Role of Relationship with Parents

Abstract: Background and Purpose: By developing new technologies, increasing the use of Computer games by children, the variety of these games, and their negative effects on children's sleep, identifying and monitoring games will be crucial. This study aimed to investigate the relationship between Computer Games addiction to sleep disorders in preschool children considering the role of moderating relationships with parents. Method: This is a correlation study. The sample of this study was 350 mothers of preschool childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…45 The results of the sign test indicated that the quality of sleep in the experimental group improved after CPRT treatment. Although there was no similar study on the effect of the treatment based on improving the parent-child interaction on the quality of sleep, the study by Mortazavi and Farhadi, 46 investigating the relationship between computer games addiction and sleep disorders in preschool children with the moderating role of communication with parents, showed a direct relationship between the occurrence of sleep disorders and their adverse effects and the destructive role of computer game addiction. In this study, the type of communication with parents and its components (acceptance of the child, rejection of the child, protective insight, negligence) were introduced as a moderating factor between sleep disorder and addiction to computer games.…”
Section: Discussionmentioning
confidence: 99%
“…45 The results of the sign test indicated that the quality of sleep in the experimental group improved after CPRT treatment. Although there was no similar study on the effect of the treatment based on improving the parent-child interaction on the quality of sleep, the study by Mortazavi and Farhadi, 46 investigating the relationship between computer games addiction and sleep disorders in preschool children with the moderating role of communication with parents, showed a direct relationship between the occurrence of sleep disorders and their adverse effects and the destructive role of computer game addiction. In this study, the type of communication with parents and its components (acceptance of the child, rejection of the child, protective insight, negligence) were introduced as a moderating factor between sleep disorder and addiction to computer games.…”
Section: Discussionmentioning
confidence: 99%